Insidious Trauma – Between the Political and the Psychoanalytical - Keini, Noga Levine; Klonover, Dr. Eyal (Advances in Social Sciences Research Journal, 2021)
The article attempts to understand the affliction known as insidious trauma and its link to social and political situations. The medical establishment finds itself hard pressed to provide an adequate response to traumas of social and political origin, rooted in oppressive regimes or environments. To the best of our knowledge the psycho-political model of recovery should take into account active resistance on the part of the individual suffering from insidious trauma. Subjectivity that is exposed to insidious trauma, but is not at the same time exposed to representations of resistance, remains external to the discourse. By assigning a name, a language and a voice to insidious trauma, the discourse is shifted from intrapsychic psychopathology to social psychopathology, thereby imparting to it both a social and a political context.